2011
DOI: 10.2217/epi.11.105
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Infinium Methylation 450K technology

Abstract: Aims: Studies of DNA methylomes hold enormous promise for biomedicine but are hampered by the technological challenges of analyzing many samples cost-effectively. Recently, a major extension of the previous Infinium HumanMethylation27 BeadChip ® (Illumina, Inc. CA, USA), called Infinium HumanMethylation450 (Infinium Methylation 450K; Illumina, Inc. CA, USA) was developed. This upgraded technology is a hybrid of two different chemical assays, the Infinium I and Infinium II assays, allowing (for 12 samples in pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
548
0
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 515 publications
(569 citation statements)
references
References 23 publications
17
548
0
4
Order By: Relevance
“…So far we have focused on methylation changes within promoters, as this region is known to be of regulatory significance. However, it is important to study if results differ had we used other gene regions, which can be assessed using data (36) generated with the more comprehensive Illumina 450k arrays (44). Consistent with our previous result, genes with age-associated changes in the TSS200 region [i.e., within 200 bp of the transcription start site (TSS)] exhibited significantly lower connectivity than their complement.…”
Section: Early and Late Life Epigenetic Drift Affects Gamp Interactomesupporting
confidence: 71%
“…So far we have focused on methylation changes within promoters, as this region is known to be of regulatory significance. However, it is important to study if results differ had we used other gene regions, which can be assessed using data (36) generated with the more comprehensive Illumina 450k arrays (44). Consistent with our previous result, genes with age-associated changes in the TSS200 region [i.e., within 200 bp of the transcription start site (TSS)] exhibited significantly lower connectivity than their complement.…”
Section: Early and Late Life Epigenetic Drift Affects Gamp Interactomesupporting
confidence: 71%
“…29,31,32 Initially we performed a technical validation of the discovery cohort data by pyrosequence analysis of converted DNA. 25,33,34 In common with previous reports and across multiple genes, these analyses confirmed and reinforced the array-derived data. 34,35,36 These analyses also showed that for the majority of regions investigated, methylation extended to include contiguous promoter-associated CpG sites.…”
Section: Discussionsupporting
confidence: 87%
“…40 b-values range from 0 (unmethylated) to 1 (fully methylated). NIMBL was used to perform 'peak-based' correction, to adjust for potential differences in array probe-type sensitivity previously reported 33 ; all comparative analyses of high-grade tumors to normal bladder controls, were performed on peak-based corrected b-values, as described by us previously. 68 Each array passed quality control assessment based upon the performance of internal controls and the distribution of b-values across all array CpGs.…”
Section: Illumina Humanmethylation450 Beadchip Array Analysesmentioning
confidence: 99%
“…This C/T polymorphism generated by the bisulfite treatment is genotyped and used to evaluate CpG methylation in the Infinium methylation assay that covers 96% of CGIs and 99% of human RefSeq genes. 47 A total of 200 ng of bisulfite converted DNA (Bs-DNA) was then used for methylation assay using Infinium HumanMethylation450 BeadChip kit according Illumina Infinium HD Methylation protocol. Briefly, this included whole genome amplification (WGA) where Bs-DNA is denatured, neutralized and incubated at 37 °C followed by enzymatic fragmentation, precipitation and resuspension in hybridization buffer.…”
Section: Methodsmentioning
confidence: 99%